2005
DOI: 10.1158/1078-0432.ccr-04-1895
|View full text |Cite
|
Sign up to set email alerts
|

MRP3, BCRP, and P-Glycoprotein Activities are Prognostic Factors in Adult Acute Myeloid Leukemia

Abstract: Purpose: P-Glycoprotein (Pgp) is associated with poor outcome in acute myeloid leukemia (AML). We have investigated other ATP-binding cassette proteins such as BCRP, MRP1, MRP2, MRP3, and MRP5 for their potential implication in chemoresistance. Experimental Design and Results: Eighty five AML patient samples were analyzed in this study. First, MRP3 function was higher in patients which had a high level of leukocytes (P = 0.01), a M5 FAB subtype (P = 0.04), and an intermediate or poor cytogenesis (P = 0.05). BC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
3
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(94 citation statements)
references
References 45 publications
4
84
3
3
Order By: Relevance
“…The negligible effect of ABCG2 overexpression on CR, different from what has been reported by other groups, 5,7,14 can be explained by the inclusion of fludarabine in the induction we used. In 3 different ABCB1-overexpressing cell-line systems, we previously demonstrated that the use of fludarabine decreases the resistance index more in the resistant sublines than in their parental ones.…”
Section: Discussioncontrasting
confidence: 78%
“…The negligible effect of ABCG2 overexpression on CR, different from what has been reported by other groups, 5,7,14 can be explained by the inclusion of fludarabine in the induction we used. In 3 different ABCB1-overexpressing cell-line systems, we previously demonstrated that the use of fludarabine decreases the resistance index more in the resistant sublines than in their parental ones.…”
Section: Discussioncontrasting
confidence: 78%
“…Using the previously described cutoff criteria, 11,14 67 and 52% of patients presented Pgp expression and activity, respectively, 65 and 62%, respectively, for MRP1 Table 1 Baseline characteristics of patients…”
Section: Results From Mdr Studiesmentioning
confidence: 99%
“…Previous studies have shown that ABC protein activities are prognostic factors in AML. 10,11,15 The role of ABC proteins has been studied in patients treated with GO at a dose of 9 mg/m 2 , and it has been shown that blast cell Pgp expression correlated with treatment failure. 16 It has also been shown that ABCG2 (BCRP) expression and activity were not associated with reduced GO activity in cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations